Aloe vera Leaf Gel in Treatment of Advanced Type 2 Diabetes Mellitus Needing Insulin Therapy: A Randomized Double-Blind Placebo-Controlled Clinical Trial - H Fallah Huseini; S Kianbakht; R Hajiaghaee; M Afkhami-Ardekani; A Bonakdaran; F Hashem Dabaghian (Institue of Medicinal Plants, ACECR, 2012)
Background: Advanced type 2 diabetes mellitus (T2DM) needing insulin therapy is a common disease. Previous studies indicate that aloe (Aloe vera L.) leaf gel may positively affect the blood glucose and lipid levels in patients with advanced T2DM needing insulin.   Objective: Evaluation of the efficacy and safety of aloe leaf gel in the treatment of type 2 diabetic patients resistant to oral synthetic anti-hyperglycemic drugs needing insulin.   Methods: In this randomized double - blind placebo-controlled clinical trial with the patients aged 40-60 years, the efficacy and safety of taking aloe leaf gel (one 300 mg capsule every 12 hours for 2 months) combined with oral synthetic anti-hyperglycemic drugs in treatment of 35 patients were evaluated and compared with the placebo group (n = 35).   Results: The aloe leaf gel lowered the blood levels of fasting glucose and glycosylated hemoglobin significantly (p = 0.041 and p = 0.023 respectively) without any significant effects on the lipid profile and liver/kidney function tests (p > 0.05) compared with placebo at the endpoint. No adverse effects were reported.  Conclusion: The results suggest that aloe leaf gel may safely improve glycemic control in patients with advanced T2DM needing insulin.